Perceptions of Economics Students on Determining Their Intention to Perform Retail Sukuk: Case study Universities in Jambi5. - Hamzah, Maulana; Ladini, Urwawuska (International Journal of Islamic Finance, 2024)
Background: Students with economic background should ideally have literacy related to the capital market and the products included in it, including sukuk. Objectives: This study aims to see the effect of accessibility, guarantees, rewards and understanding of sharia on students' interest in buying sukuk, especially in this context retail sukuk. Novelty: Compared to previous research, this research focuses more on how students in Jambi, especially those majoring in economics and related fields, practicing investment, especially in sukuk. Research Methodology: This study uses a quantitative approach using the PLS-SEM (Partial Least Square-Structural Equation Modeling) analysis tool. This research involved 598 respondents from students of economics which came from various campuses in Jambi province. Findings: The results of the study show that all valid variables, convenience, security, ujroh and shariah variables have a 77% influence on student interest as indicated by the value of r square. Sharia latent variable is the variable that has the greatest influence among other variables. Implication: Based on the research results, the socialization of sharia values ​​in sukuk needs to be encouraged by related parties to increase the active role of students in sharia investment59